Evaluating the Effectiveness of Assessment Methods in Moulay Ismail University: Insights from Postgraduate Students - OUCHAIB, Abdelaziz; El Kasri, Anouar Mohamed; Messouab, Imad (International Journal of Language and Literary Studies, 2024)
The present study evaluates and measures the effectiveness of the assessment practices promoted in the LMD system (Licence, Master and Doctorate) implemented in Moroccan universities from the perspective of postgraduate students at the open-access institutions affiliated with Moulay Ismail University (UMI), namely the School of Arts and Humanities (FLSH), the School of Sciences (FS), the School of Law, Economics and Social Sciences (FSJES), and the Polydisciplinary School of Errachidia (FP). To achieve this objective, the study deployed a mixed-methods; two-phase case study design. In the initial quantitative phase, a questionnaire was administered to 742 postgraduate students to investigate their evaluation of the assessment practices promoted in the LMD system. Further, in the follow-up qualitative phase, interviews with 28 doctoral students were conducted to extend and explain the quantitative results. It has been found that continuous assessment is not used by most teachers and that the final exams are the only method used by professors to assess students' performance. Likewise, the study revealed that the compensation system negatively affects the quality of higher education training by allowing students to pass and study more difficult modules while they have not learned the necessary prerequisites from the basic modules. Equally significant, the study found that most students struggle with the end-of-study research module, blaming their supervisors who do not provide sufficient or appropriate supervision. In conclusion, this paper offers several pedagogical implications for stakeholders and teachers at the UMI to make assessment more effective.